The Influence of Ownership Structure, Non-Performing Loans, and Long-Term Debt on the Financial Performance of Banking Companies in ASEAN - Luana, Mona; Adam, Mohamad; Widiyanti, Marlina; Fuadah, Lukluk (International Journal Labs, 2024)
The purpose of this study is to obtain empirical evidence of the managerial ownership and institutional ownership, non-performing loans, and long-term debt ratio on the ASEAN Banking Company firms. The sampling technique used purposive sampling, the research samples obtained totaled 40 companies with a research period from 2019-2023 so that there were 200 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is multiple regression analysis method. The results showed that NPL and Institutional ownership has a significant negative effect, managerial ownership and long-term debt ratio has no significant effect on firm’s perfromance. The implication of this research is that companies must pay attention to that NPL and Institutional ownership and those that can affect profitabilty so that company performance can increase.